Permeability Changes Resulting from Quartz Precipitation and Dissolution around Upper Crustal Intrusions - Samuel W. Scott; Thomas Driesner (Geofluids)
It has long been recognized that quartz precipitation from circulating hydrothermal fluids may reduce porosity and permeability near intrusions. However, the magnitude of permeability changes and potential feedbacks between flow, heat transfer, and quartz precipitation/dissolution remain largely unquantified. Here, we present numerical simulations of fluid convection around upper crustal intrusions which explicitly incorporate the feedback between quartz solubility and rock permeability. As groundwater is heated to ~350°C, silica dissolves from the host rock, increasing porosity and permeability. Further heating to supercritical conditions leads to intensive quartz precipitation and consequent permeability reduction. The initial host rock permeability and porosity are found to be main controls on the magnitude and timescales of permeability changes. While the permeability changes induced by quartz precipitation are moderate in host rocks with a primary porosity ≥ 0.05, quartz precipitation may reduce rock permeability by more than an order of magnitude in host rocks with a primary porosity of 0.025. Zones of quartz precipitation transiently change locations as the intrusion cools, thereby limiting the clogging effect, except for host rocks with low initial porosity. This permeability reduction occurs in timescales of hundreds of years in host rocks with initial high permeability and thousands of years in host rocks with intermediate permeability.